Beneficial microbial consortium improves winter rye performance by modulating bacterial communities in the rhizosphere and enhancing plant nutrient acquisition - Behr, Jan Helge; Kampouris, Ioannis D.; Babin, Doreen; Sommermann, Loreen; Francioli, Davide; Kuhl-Nagel, Theresa; Chowdhury, Soumitra Paul; Geistlinger, Joerg; Smalla, Kornelia; Neumann, Günter; Grosch, Rita (Frontiers in Plant Science, 2023)
The beneficial effect of microbial consortium application on plants is strongly affected by soil conditions, which are influenced by farming practices. The establishment of microbial inoculants in the rhizosphere is a prerequisite for successful plant-microorganism interactions. This study investigated whether a consortium of beneficial microorganisms establishes in the rhizosphere of a winter crop during the vegetation period, including the winter growing season. In addition, we aimed for a better understanding of its effect on plant performance under different farming practices. Winter rye plants grown in a long-time field trial under conventional or organic farming practices were inoculated after plant emergence in autumn with a microbial consortium containing Pseudomonas sp. (RU47), Bacillus atrophaeus (ABi03) and Trichoderma harzianum (OMG16). The density of the microbial inoculants in the rhizosphere and root-associated soil was quantified in autumn and the following spring. Furthermore, the influence of the consortium on plant performance and on the rhizosphere bacterial community assembly was investigated using a multidisciplinary approach. Selective plating showed a high colonization density of individual microorganisms of the consortium in the rhizosphere and root-associated soil of winter rye throughout its early growth cycle. 16S rRNA gene amplicon sequencing showed that the farming practice affected mainly the rhizosphere bacterial communities in autumn and spring. However, the microbial consortium inoculated altered also the bacterial community composition at each sampling time point, especially at the beginning of the new growing season in spring. Inoculation of winter rye with the microbial consortium significantly improved the plant nutrient status and performance especially under organic farming. In summary, the microbial consortium showed sufficient efficacy throughout vegetation dormancy when inoculated in autumn and contributed to better plant performance, indicating the potential of microbe-based solutions in organic farming where nutrient availability is limited.